Keeping tabs on your cooperating partners: a coalition perspective on international organizations. Issue 3 (30th August 2018) - Kleine, Mareike
Abstract : This article argues that opportunities for unilateral influence within international bureaucracies create a delegation problem akin to that in coalition governments. Parties in coalitions that suspect each another of diverting from the coalition bargain avail themselves of mechanisms, such as junior ministers and parliamentary scrutiny, to monitor their coalition partners' actions within the executive. Similarly, states that suspect cooperating partners of abusing their unilateral influence within the bureaucracy employ mechanisms, reminiscent of those in coalition governments, in order to 'keep tabs' on one another. I illustrate the plausibility of this claim using the case of the European Commission. However, this delegation problem of interstate control can be expected to apply more widely. The article has implications for the study of international organization, international delegation and informal governance.